Implementasi Keamanan Jaringan Komputer Local Area Network Menggunakan Access Control List pada Perusahaan X - Agung Tri Laksono; M. Alvian Habib Nasution (Universitas Budi Darma, 2020)
In Company X, the use of the internet is a demand for workers. Therefore, an internet network is very much needed in a Company X. The absence of restrictions in the use of the internet network can interfere with the security and misuse of the internet network, for this reason the arrangements in the internet network are designed. One method used is the Virtual Local Area Network (VLAN) Access Control List (ACL) method that is applied to Company X. The Vlan Access Control List method is one of the techniques for requesting an internet network access or data communication and sending a number of data packets from one computer to another. The author resets the results proving that the Vlan Access Control List with the filtering and sharing method of internet connection users can filter and identify users who have restricted access to access other users or to servers in Company X to improve data security.